(untitled) (Raparin Journal of Humanities (RJH), 2023)
African American playwrights always tend to manifest their African heritage and culture (Afrocentrism) through their plays. In other words, Afrocentrism means African centered-ness. Afrocentrism or Afrocentricity basically focuses on Africans and places African history, heritage and culture at the heart of any analysis. One of the Afrocentric writers is Alice Childress whose texts generally center on the devastating effects of racial discrimination, sexism and classism on women of colour. This study is principally concerned with the one-act play of Alice Childress, Wine in the Wilderness, which was written in 1964 and was first performed in 1969 in Boston, Massachusetts, as part of the series, “On Being Black”. In Wine in the Wilderness, Childress is bound by history and tradition since several references can be found in the play that considers Africa as a homeland and wellspring of strength. This paper investigates some questions such as: how does Alice Childress employ the Afrocentric value in the play? What is the purpose of Afrocentrism in the play? Who best represents Afrocentrism throughout the play? This paper delineates that Tommy, as an undereducated heroine and as a true Afrocentrist female in the play, is proud of her black culture and her blackness.